Effects and Mechanisms of Cognitive, Aerobic Exercise, and Combined Training on Cognition, Health, and Brain Outcomes in Physically Inactive Older Adults: The Projecte Moviment Protocol - Castells-Sánchez, Alba; Roig-Coll, Francesca; Lamonja-Vicente, Noemí; Altés-Magret, Marina; Torán-Monserrat, Pere; Via, Marc; García-Molina, Alberto; Tormos, José Maria; Heras, Antonio; Alzamora, Maite T.; Forés, Rosa; Pera, Guillem; et al. (Frontiers in Aging Neuroscience, 2019)
Introduction: Age-related health, brain and cognitive impairment is a great challenge in current society. Cognitive training, aerobic exercise and their combination have been shown to benefit health, brain, cognition and psychological status in healthy older adults. Inconsistent results across studies may be related to several variables. We need to better identify cognitive changes, individual variables that may predict the effect of these interventions and changes in structural and functional brain outcomes as well as physiological molecular correlates that may be mediating these effects. Projecte Moviment is a multi-domain randomized trial examining the effect of these interventions applied 5 days per week for 3 months compared to a passive control group. The aim of this paper is to describe the sample, procedures and planned analyses. Methods: 140 healthy physically inactive older adults will be randomly assigned to computerized cognitive training (CCT), aerobic exercise (AE), combined training (COMB) or a control group. The intervention consists of a 3-month home-based program 5 days per week in sessions of 45 minutes. Data from cognitive, physical and psychological tests, cardiovascular risk factors, structural and functional brain scans and blood samples will be obtained before and after the intervention. Results: Effects of the interventions on cognitive outcomes will be described in intention-to-treat and per protocol analyses. We will also analyze potential genetic, demographic, brain and physiological molecular correlates that may predict the effects of intervention as well as the association between cognitive effects and changes in these variables using the per protocol sample. Discussion: Projecte Moviment is a multi-domain intervention trial based on prior evidence that aims to understand the effects of CCT, AE and COMB on cognitive and psychological outcomes compared to a passive control group and to determine related biological correlates and predictors of the intervention effects. (ClinicalTrials.gov; identifier: NCT03123900)